31: Treatment and Reduction of Anxiety and Pain in Pediatric Emergency Department: 'Trapped' Survey; A Pediatric Emergency Research Canada Study. Issue 6 (1st June 2014) - Trottier, ED; Gravel, J; Lemay, S; Ali, S
Abstract: BACKGROUND: Resources available to manage children's pain in the pediatric emergency department (PED) may be sub-optimal. OBJECTIVES: a) To evaluate currently available resources for pediatric pain management in Canadian PEDs and b) to evaluate which currently unavailable resources were felt to be most amenable to rapid implementation. DESIGN/METHODS: This cross sectional survey evaluated pain and anxiety management policies and procedures used in PEDs across Canada. All attendees of the 2012 Pediatric Emergency Research Canada (PERC) annual conference (>50 pediatric emergency physicians) were asked to provide a comprehensive list of pain and anxiety management interventions available at their institution. This information was then used as the basis for creation for this survey, along with expert opinion and literature review. The study tool was pilot tested for face and content validity, and data were collected via an electronic survey. The PERC site representative for each pediatric hospital across Canada was contacted to identify the most appropriate administrator to complete the survey. RESULTS: We had an 80% (12 of 15) response rate. Most settings (58%) did not have access to a child life specialist; 17% thought it could be easily implemented in their centre. The most frequently used distraction method was TV/video recordings (83%). Fifty-eight percent of the centre offered the parental lap/sitting position for IV insertion; another 33% felt that this could be easily implemented in their center. Local anesthetic use before IV insertion was employed by 83%; all remaining centres reported that this could be easily organised in their ED. Most settings used nurse-initiated protocols for local anesthetic (67%), acetaminophen (100%), ibuprofen (100%) and opioids (39%). Intranasal fentanyl was used in 58% of the centres; another 33% of centres felt it could be easily implemented. Only 36% of centres used nitrous oxide; all remaining centres felt it would be difficult to use. Biers blocks were minimally used (20%), and were perceived as difficult to implement by 50%. CONCLUSIONS: There is a wide variability in resources available at the different PEDs across Canada. We have identified some known, effective techniques for pain management (parental lap/sitting, local anesthetic for IV insertion, intranasal fentanyl) that were felt to be easy to implement. By implementing these changes first, clinicians and administrators may find greater success in addressing current deficits in children's pain management in the PED.